Developing indigenous tourism in the bomas: critiquing issues from within the Maasai community in Tanzania. Issue 3 (4th May 2019) - Melubo, Kokel; Carr, Anna
ABSTRACT: With safari attractions dominating the African tourism sector, many tourism studies in Africa have focused on wildlife and wilderness resourced-based tourism, with a secondary body of literature exploring cultural aspects of tourism. Recently many countries in the region, including Tanzania, have started to recognize the potential for stand-alone, culture-based tourism to diversify the tourism industry and for rural, economic development purposes. Drawing upon insights from local stakeholders, primarily members of the Maasai community this study identifies the critical challenges for providing indigenous cultural tourism in the Ngorongoro Conservation Area, Tanzania. Qualitative data for the study were collected through interviews and site visits to eight Maasai bomas (cultural tourism villages or settlements). Thematic analysis of the interviews revealed significant limiting factors affecting the development of indigenous cultural tourism amongst Maasai in Tanzania. The findings indicate that achieving success in indigenous cultural tourism is therefore challenging, and needs to incorporate specific community-based strategies which can facilitate the development of Maasai cultural tourism.